Total minimally invasive McKeown esophagectomy in an esophageal cancer patient with situs inversus totalis: A case report - Chu‐Long Xie; Jing‐Sheng Cai; Zi‐Hui Tan; Jie Yang; Hao‐Xian Yang (Thoracic Cancer)
Situs inversus totalis (SIT) is an extremely rare anomaly characterized by a left‐to‐right reversal of all the thoracic and abdominal organs. Only 11 cases of esophageal cancer with SIT have been reported worldwide, most of which underwent hybrid minimally invasive esophagectomy (MIE) but not total MIE. Here, we report a case of esophageal cancer with SIT successfully treated by total MIE, with a right lateral‐prone position adopted during the thoracic procedure. The relevant literature is also discussed and reviewed.